2009
DOI: 10.1007/s11999-008-0567-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Sterile Meniscal Allograft in an Ovine Model

Abstract: Meniscus transplantation is indicated for persistent pain in a meniscectomized knee. Currently, grafts are prepared aseptically, which provides limited protection against donor-derived infection. The performance of a novel, sterilized meniscus was compared with an aseptically prepared one in an experimental model. Twenty-two sheep were divided into three groups: aseptic meniscal allograft, sterile meniscal allograft, and medial meniscectomy. Animals were euthanized 2 and 4 months after surgery. Meniscal assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The ovine stifle has often been the joint of choice to evaluate surgical and medical therapeutics of osteoarthritis (OA), meniscal pathology, injuries of cruciate ligaments and collateral ligaments . Knowledge of the anatomy of the joint is useful to plan surgical access and to assess the progress of the disease in research studies, either by gross anatomy or imaging techniques.…”
mentioning
confidence: 99%
“…The ovine stifle has often been the joint of choice to evaluate surgical and medical therapeutics of osteoarthritis (OA), meniscal pathology, injuries of cruciate ligaments and collateral ligaments . Knowledge of the anatomy of the joint is useful to plan surgical access and to assess the progress of the disease in research studies, either by gross anatomy or imaging techniques.…”
mentioning
confidence: 99%
“…Meniscal replacement with meniscal allograft provides some protection, albeit incomplete, against joint damage after a meniscectomy 181,182 . The severity of chondral damage in the allograft knees in sheep could not be distinguished from meniscectomized joints 183 . Immediate meniscal transplantation in rabbits has a protective effect on articular cartilage in the long term whereas delayed transplantation leads to even more degenerative changes than meniscectomy alone 184 .…”
Section: Results Of Meniscal Transplantsmentioning
confidence: 86%
“…To succeed, however, it must first bond to the remaining structure to facilitate revascularization and then repopulate with cells that will maintain the appropriate extracellular matrix (Stone et al ., ). Meniscal allograft decelerates the progression of chondral damage in meniscectomized knees (McNickle et al ., ) and this protective effect has been tested in various animal models.…”
Section: Meniscal Replacement and Regenerationmentioning
confidence: 99%
“…In the sheep model, allogeneic frozen menisci were implanted in the knee joints and showed a chondroprotective effect in comparison to meniscectomy; the graft was repopulated by the host with cells derived from the synovium, particularly at the capsular and femoral surfaces, but the decrease in proteoglycan content persisted over time, suggesting an incomplete cell migration into the meniscal allograft (McNickle et al ., ). In another study, fresh allogeneic menisci were implanted but, although this model demonstrated significant improvement compared to meniscectomy, progressive cartilage degeneration still occurred (Kelly et al ., ).…”
Section: Meniscal Replacement and Regenerationmentioning
confidence: 99%